Exploring Strategic Choices of Airlines: A Study in Turkish Air Transport Industry - Hüseyin Önder Aldemir (Universiti Sains Malaysia, 2021)
Inter-firm competition in the field of aviation, which accelerates through liberalisation and globalisation trends, has been investigated by numerous studies in the post-deregulation era; however, it has not been adequately addressed in Turkish aviation market. The aim of this study is to unveil the business strategies and strategic typologies of Turkish passenger carriers, as well as the degree of involvement of firms in the strategic planning process, the current outlook, and the competitive structure of the Turkish passenger air transport industry. The research is designed in a way to collect data through interviews with senior executives of the airlines. In terms of findings, the study concludes that five scheduled airlines and three charter airlines have attempted to implement more than one generic strategy at the same time as an “integrated cost and differentiation strategy,” with the primary strategy being cost leadership. Moreover, the passenger carriers in question displayed the features of “analysers-defenders” mainly linked to the competitive typology viewpoint. This study is believed to lead to a deeper understanding of potential explanations why companies have made specific strategic choices regarding generic strategies and strategic approaches. Regulators, individual companies operating in the aviation industry and prospective companies, investors, etc. can use the results of the study to regulate the market, better understand their competitors, set their priorities and plans, evaluate, and assess the market.